Think glocally, act glocally: a culture-centric comment on Leung, Bhagat, Buchan, Erez and Gibson (2005) - Gould, Stephen J; Grein, Andreas F (Journal of International Business Studies, 2009)
Culture is a critical variable in international business (IB), and Leung, Bhagat, Buchan, Erez and Gibson (2005) enrich our understanding of its role. However, that said, their framing of this variable conflates the role of national culture (NC), a particular form of culture, with culture itself, a more pivotal, holistic and central construct. This paper, by commenting on and critiquing their approach, seeks to shift the theoretical center of gravity from a NC-centric paradigm to a culture-centric, constructivist one, and from a top-down, bottom-up view to a flatter, glocalized one. Implications are provided which suggest that research should address cultural processes of patterning and production, as well as cultural forms, such as global communities and global culture (GC), which share with or even capture the spotlight from NC as a focus for studying and developing IB cultural theory.